'Treatment No Less Favorable' and the Future of National Treatment Obligation in GATT Article III:4 after EC–Seal Products. Issue 1 (1st June 2015) - DU, MING
Abstract: The national treatment (NT) obligation embodied in Article III:4 of the GATT 1994 has been long marked by legal indeterminacy. Recently, the WTO Appellate Body has shed some fresh light on how the NT obligation should be interpreted in EC–Seal Products . The Appellate Body's report on EC–Seal Products and other recent developments in WTO case law have fundamentally reshaped our collective understanding of the NT obligation. The purpose of this article is to take stock of what we have known about the NT obligation in GATT Article III:4 after EC–Seal Products, as well as identifying some lingering uncertainties. This paper argues that the boundary of the NT obligation in GATT Article III:4 will be largely determined by how the Appellate Body deals with three big issues identified in this article in future disputes.